Collaborative information behavior [ user engagement and communication sharing - Foster, Jonathan , 1965- (Gale virtual reference library, 2010)
"This book coordinates and integrates current research and practices in the area of collaborative information behavior, providing information on empirical research findings, theoretical frameworks, and models relevant to understanding collaborative information behavior"-- Provided by publisher